Formulation Variables Effect on Gelation Temperature of Nefopam Hydrochloride intranasal in Situ Gel (Conference Paper) # - Alabdly, Ammar; J. Kassab, Hanan (Iraqi Journal of Pharmaceutical Sciences, 2023)
Nefopam (N.F.) HCl is a non-narcotic centrally-acting, non-opioid benzoxazocine analgesic to relieve acute and chronic pain. It exhibits low bioavailability (about 36%) due to its first-pass degradation in the liver. Intranasal administration has been used as a new route for targeting active brain sites and enhancing the bioavailability of N.F. HCl bypassing hepatic metabolism. In situ gel of N.F. HCl was prepared by the cold method using different concentrations of Poloxamer 407, Poloxamer 188, HPMC K4M, Carbapol 934, and Hyaluronic acid polymers. The results show that identification tests are superimposed with references, solubility study shows that N.F. HCl is suitable to be administered intranasally; Compatibility studies reveal incompatibility of Nefopam HCl with HPMC K4M and Carbapol 934; meanwhile, no interaction with Methylcellulose and Hyaluronic acid. In conclusion, the obtained results revealed the incredible ability of the produced N.F. HCl intranasal in situ gel is intended to enhance drug bioavailability bypassing the metabolizing effect of the liver that N.F. HCl is facing when given orally.